Tough choices for an agile open source international development project: the Libre LAS Case. Issue 2 (November 2018) - McDowell, Andrew; Drechsler, Andreas
Abstract In June 2010, the Food and Agriculture Organization (FAO) of the United Nations (UN) started a three-year trust fund project to develop and pilot open source cadastre and registration software. This project was called Libre Land Administration System (Libre LAS), and its aim was to make computerised cadastre and registration systems more affordable and more sustainable in developing countries. The first stage of the Libre LAS project was undertaken at FAO headquarters (HQ) in Rome. Generic cadastre and registration processes were defined and software requirements and software architecture documents prepared. Development of the Libre LAS software began in early 2011. An international team of software developers assembled at FAO HQ and proceeded to create the generic software platform using an Agile Scrum methodology. By early 2012, the first release of Libre LAS was ready and pilot implementations began in Ghana, Nepal, and Samoa to validate and prove the Libre LAS concept. This case study tracks the initial development and implementation of Libre LAS in the pilot countries from 2011 to late 2012. It is presented from the standpoint of Brett, the Libre LAS Project Coordinator, and discusses organisational, cultural, stakeholder, and financial issues that conspired to derail the project. Ultimately, Brett is left to make some tough decisions around the pilot implementations to ensure the success of the overall project.